Microsurgery for ARUBA Trial (A Randomized Trial of Unruptured Brain Arteriovenous Malformation)–Eligible Unruptured Brain Arteriovenous Malformations. Issue 1 (January 2017) - Wong, Johnny; Slomovic, Alana; Ibrahim, George; Radovanovic, Ivan; Tymianski, Michael
Abstract : Background and Purpose—: The management of unruptured brain arteriovenous malformations (ubAVMs) remains controversial despite ARUBA trial (A Randomized Trial of Unruptured Brain Arteriovenous Malformation), a controlled trial that suggested superiority of conservative management over intervention. However, microsurgery occurred in only 14.9% of ARUBA intervention cases, raising concerns about the study's generalizability. Our purpose was to evaluate whether, in a larger ARUBA-eligible ubAVM population, microsurgery produces acceptable outcomes. Methods—: Demographic data, AVM characteristics, and treatment outcomes were evaluated in 155 ARUBA-eligible bAVMs treated with microsurgery between 1994 and 2014. Outcomes were rates of early disabling deficits and permanent disabling deficits with modified Rankin Scale score ≥3 or any permanent neurological deficits with modified Rankin Scale score ≥1. Covariates associated with outcomes were determined by regression analysis. Results—: Of 977 AVM patients, 155 ARUBA-eligible patients had microsurgical resection (71.6% surgery only and 25.2% with preoperative embolization). Mean follow-up was 36.1 months. Complete obliteration was achieved in 94.2% after initial surgery and 98.1% on final angiography. Early disabling deficits and permanent disabling deficits occurred in 12.3% and 4.5%, respectively, whereas any permanent neurological deficit (modified Rankin Scale score ≥1) occurred in 16.1%. Among ubAVM of Spetzler–Martin grades 1 and 2, complete obliteration occurred in 99.2%, with early disabling deficits and permanent disabling deficits occurring in 9.3% and 3.4%, respectively. Major bleeding was the only significant predictor of early disabling deficits on multivariate analysis ( P <0.001). Conclusions—: Microsurgery in this cohort produced less disabling deficits than ARUBA with similar morbidity and AVM obliteration as other cohort series. This disparity between our results and ARUBA suggests that future controlled trials should focus on the safety and efficacy of microsurgery with or without adjunctive embolization in carefully selected ubAVM patients.